Pembatalan Sertipikat Hak Milik Atas Tanah Oleh Peradilan Tata Usaha Negara Di Pengadilan Tata Usaha Negara Palembang - Baranyanan, Soeleman Djaiz (CAPITAN: Constitutional Law & Administrative Law Review, 2024)
This article examines legal issues, namely the cancellation of certificates of ownership of land in order to achieve legal certainty (Inkracht) and its implementation. The legal basis used is Law Number 5 of 1986 and SEMA No. 2 of 1991, concerning PTUN. Where the Decision at the Cassation level of the Supreme Court of the Republic of Indonesia Number 384 K/TUN/2013 in the name of Megawaty Delvin Tandiari (Plaintiff) is firm and clear in the main case as the party who won and was granted the Plaintiff's lawsuit, ordering the Head of the Land Office (Kakantah) to carry out the revocation , cancel the certificate of Land Ownership Decree, in the name of M. Riduwan Thamrin (Defendant), Number 1657/Kelurahan 20 Ilir D II Measurement Letter Number 34/20 Ilir D II/2012 dated 26 June 2012 Kemuning District covering an area of ​​750 M2, Basis The law used is the Basic Agrarian Law (UUPA), Law Number 3 of 2011 Regulation of the Head of the National Land Agency (PKBPN), provisions of Government Regulation no. 9 of 1999 and Regulation of the Head of BPN no. 11 of 2016, concerning the implementation of Administrative Court decisions State by BPN. And the execution of decisions is regulated in HAPTUN (vide article 116 paragraph 1-2 of Law no. 5 of 1986). This research uses the theory of legal protection and justice. And the Contrario Actus principle means that the issuing official has the authority to issue a decision and also has the authority to revoke the decision issued. This type of thesis research is normative legal research and field research, which uses analytical, legislative and field research approaches. Efforts to minimize the occurrence of object disputes due to the existence of two certificates on the same plot of land, by complying with applicable regulations and good cooperation between agencies to deepen knowledge in the field of law and increase discipline in the National Land Agency (BPN) Office system. The legal concept in the future must be more firm in providing sanctions if there are individuals who seek profit so that legal objectives can be achieved, namely legal certainty regarding the status of ownership rights, and the purpose of land registration is to obtain the legal status of the land, with cancellation the legal status of the land will be lost.